Extending the Consumer Acceptance of Technology (CAT) Model: Antecedents and Mediators - Butcher, Luke; Phau, Ian; Marchegiani, Chris (Australian and New Zealand Marketing Academy, 2012)
The aims of this paper is three-fold: (a) to propose a new extended consumer acceptance of technology (CAT) model with an addition of more appropriate emotion measures and the inclusion of a financial value for money construct, (b) to broaden the conceptualization of consumer adoption of technology; and (c) to clarify the role of key mediators in the model. A set of hypotheses is proposed with findings pointing towards a multidimensional approach to behavioural intentions and a chiefly different model to those proposed in extant literature.